Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12934-016-0612-6
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene production by Escherichia coli through the exogenous mevalonate pathway with reduced formation of fermentation byproducts

Abstract: BackgroundIsoprene, a volatile C5 hydrocarbon, is an important platform chemical used in the manufacturing of synthetic rubber for tires and various other applications, such as elastomers and adhesives.ResultsIn this study, Escherichia coli MG1655 harboring Populus trichocarpa isoprene synthase (PtispS) and the exogenous mevalonate (MVA) pathway produced 80 mg/L isoprene. Codon optimization and optimal expression of the ispS gene via adjustment of the RBS strength and inducer concentration increased isoprene p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 25 publications
0
51
0
Order By: Relevance
“…Blocking pathways that catabolize acetyl‐CoA is an effective approach for obtaining acetyl‐CoA derived compounds (Dong et al, 2017; Wu & Eiteman, 2016). Acetate formation is another pathway to reduce the supply of acetyl‐CoA (Kim et al, 2016; Parimi, Durie, Wu, Niyas, & Eiteman, 2017; Saini, Wang, Chiang, & Chao, 2014). Acetyl‐CoA is metabolized by phosphate acetyltransferase, which is encoded by pta , and the resultant product (acetyl‐phosphate) is converted to acetate by acetate kinase ( ackA ) Pyruvate dehydrogenase ( poxB ) produces acetate from pyruvate, a precursor of acetyl‐CoA.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking pathways that catabolize acetyl‐CoA is an effective approach for obtaining acetyl‐CoA derived compounds (Dong et al, 2017; Wu & Eiteman, 2016). Acetate formation is another pathway to reduce the supply of acetyl‐CoA (Kim et al, 2016; Parimi, Durie, Wu, Niyas, & Eiteman, 2017; Saini, Wang, Chiang, & Chao, 2014). Acetyl‐CoA is metabolized by phosphate acetyltransferase, which is encoded by pta , and the resultant product (acetyl‐phosphate) is converted to acetate by acetate kinase ( ackA ) Pyruvate dehydrogenase ( poxB ) produces acetate from pyruvate, a precursor of acetyl‐CoA.…”
Section: Discussionmentioning
confidence: 99%
“…The production of isoprene was further improved in E. coli MG1655 and BL21 using 5‐L fed‐batch cultivation and a two‐vector system (pTS‐sPt‐MVA and pS‐NA). This improvement is considered to be derived from the increased supply of IPP and DMAPP from pS‐NA through augmentation of the MVA pathway, resulting in high levels of isoprenoid compounds such as isoprene and lycopene [16,17]. Based on these results, we further tested a 300‐L scale‐up fermentation process with the two‐vector system using E. coli BL21 for 72‐h cultivation to improve isoprene production.…”
Section: Discussionmentioning
confidence: 99%
“…[16] suggested that the whole MVA pathway of pS‐NA could provide a sufficient amount of isopentenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP). Therefore, the strains were additionally transfected with the plasmid pTS‐sPt‐MVA derived from pTrc99K, encoding isoprene synthase from Populus trichocarpa and the MVA pathway operon from pS‐NA [17].…”
Section: Methodsmentioning
confidence: 99%
“…In different studies, the measured k cat values of IspS from kudzu were different, and variable isoprene production was obtained (Table 1 ). In a recent study, more IspSs from poplar were identified, and an approximately 3-fold isoprene production increase was detected (Table 1 ) (Kim et al 2016 ). Novel IspS enzymes from other plants ( Ipomoea batatas , Mangifera indica , Elaeocarpus photiniifolius , and Mucuna pruriens ) have been identified through genome mining, and high isoprene production has been detected (Table 1 ) (Ilmen et al 2015 ).…”
Section: Use Of Isps For Isoprene Productionmentioning
confidence: 98%